The Examination of the Relationship Between Foreign Direct Investment and Trade in Turkey: ARDL Approach - Ilham, Karimov Mehman; Vaqif, Nesirov Elcin; Calal, Zeynalli Elay (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
This paper is aimed to examine the effect of Foreign Direct Investment inflow on Trade (Export, Import) in Turkey. The study copes the time span from 2006 Q2 to 2019 Q4. The time series datasets, those are retrieved from CBT and FRED database are used in applied econometrical methods such as ADF, PP, Zivot Andrews Unit Root Tests, ARDL bounds testing approach, and the Granger Causality tests, to accomplish the statistical part of the research. Based on the findings, it was supported that there was a positive relationship between FDI and Trade. Additionally, the outputs of Granger causality test indicated that there is a unidirectional causality running from FDI to Trade (Export and Import).